Leaching of N derived from the soil and from [(15NH4) 2SO4] fertilizer during the growth cycle of bean plants - Caballero, Segundo S. Urquiaga; Libardi, Paulo Leonel; Reichardt, Klaus; Moraes, Sérgio O.; Victória, Reynaldo L. (Pesquisa Agropecuaria Brasileira, 2014)
In an Oxic Paleudalf ("Terra Roxa Estruturada") soil located in Piracicaba, São Paulo, the dynamics of soil total-N and N derived from fertilizer (ammonium sulphate - 15N) in the soil solution during a bean (Phaseolus vulgaris, L.) crop 'Carioca' growth in the Autumn period (April-July), was studied. Nitrogen losses due to leaching beyond 120cm of depth were estimated. The crop was fertilized with 42 kg/ha of N using ammonium sulphate, highly enriched with 15N (56,111% 15N atoms). The fertilization was made in two stages: 1/3 was applied six days after germination (DAG) and the rest 26 DAG. The soil solution was sampled in situ, using extractors placed in the following depths of profile: 45 cm, 75 cm, 105 cm and 135 cm. The samples were accumulated during each of five periods of 20 days (0-6, 6-2 26-46, 46-66 and 66-86 DAG). In these samples the total-nitrogen was determined, and percentage 15N atoms to determine the N derived from fertilizer. It was found that: 1) during the cropping period the average total-nitrogen concentration and N derived from fertilizer decreased markedly with soil depth, being very small (15 ppm and 0,048 ppm, respectively) at 105/135 cm of depth and, 2) during the crop development under minimal drainage conditions only 3 g/ha of total nitrogen and 3.04 mg/ha of N derived from fertilizer were leached beyond the 120 cm of depth.